Detection of Single Nucleotide Polymorphism of Holandric Genes and Association with Sperm Nuclear Maturity in Bovines - Kaur, Amanpreet; Mukhopadhyay, Chandra Sekhar; Arora, Jaspreet Singh; Brah, Gurvinder Singh; Kaur, Simarjeet; Jamir, Jongmatoshi C (Indian Journal of Dairy Science, 2014)
Implementation of a successful cattle breeding program relies on selection of genetically superior and tested males against various andrological anomalies. In the present project, single stranded conformation polymorphism (SSCP) of holandric genes viz. ubiquitin specific protease, Y-linked (USPY) and RNA binding motif Y-linked (RBMY) was studied for associating with spermatological attributes (sperm chromatin maturity, semen volume, initial motility) in cattle (10 HF crossbred) and buffalo (10 Murrah). The SSCP band patterns revealed species specific variation only in two primer-pairs (US2 and US3) of USPY gene. The maximum and minimum values of percent immature sperm were ranging between 0.392 to 2.586 in cattle and from 0.901 to 4.000 in buffalo. The per cent immature spermatozoa in the ejaculates did not differ significantly either for species or for the categories (acceptable and unacceptable semen donors). The average immature sperm count was the least in buffalo ejaculates (1.383 Â± 0.176). The correlation coefficient was found negative between the spermatological parameters (volume and initial motility) and the immature sperm yield in both cattle and buffalo ejaculates. It indicates that the immature sperm production might be negatively associated with semen volume and initial motility of the spermatozoa.